Literasi Parenting Style Ditinjau dari Komunikasi Gender dan Media pada Pembinaan Kesejahteraan Keluarga Pondok Kopi - Putri, Dianingtyas Murtanti; Kurnia, Ari; Kania, Dessy; Dedees, Adek Risma; Malik, Asmiati Abdul; Apriyanti, Maya; Sunarti, Sunarti (LPkM Universitas Bakrie, 2025)
Improving the quality of human resources (HR) depends on the parenting styles applied. Implementing incorrect parenting styles can impact the cognitive, affective, and conative aspects of an individual. When parents' educational approaches are influenced by traditional views on gender roles, gender stereotypes can unintentionally be integrated into child-rearing, in this case with adolescents. This can lead to inequality and create unhealthy parenting styles. Recognizing this, there is a need for literacy on parenting styles reviewed from the perspective of gender communication and media for parents and adolescents. Through Community Service (PkM) activities, the focus is to provide knowledge about parenting styles in the digital communication era and how to implement soft skills such as effective communication with teenagers. Subsequently, participants can apply three pillars in building a good relationship between parents and their teenagers, namely empathy, tolerance, and loyalty. This activity is aimed at parents with teenagers at the Family Welfare Development (PKK) in Pondok Kopi, East Jakarta. Therefore, this activity is needed to increase awareness and knowledge of the participants about Generation Z's attitudes and behaviors. Furthermore, the results from the post-test showed that participants were very enthusiastic about participating in this activity and expressed a desire for more such events to further explore Generation Z from the perspective of communication psychology.